Volcanic rocks from the Central and Southern Palawan Ophiolites, Philippines: Tectonic and mantle heterogeneity constraints. Issue 4 (1st December 2020) - Gibaga, Cris Reven L.; Arcilla, Carlo A.; Hoang, Nguyen
Graphical abstract: Abstract: Recent studies suggest the existence of two ophiolites in Palawan Island: the Central Palawan Ophiolite (CPO) and the Southern Palawan Ophiolite (SPO). New geochemical data in this study from the volcanic rocks of the Palawan ophiolites further support this interpretation. The CPO lavas have back-arc basin basalt (BABB) affinities with LILE enrichment and depleted LREE. In contrast, volcanic rocks of the SPO are geochemically diverse, including low-TiO2 boninitic andesites, MORB-like lavas, and high TiO2, high Nb lavas. Sr, Nd and Pb isotopic ratios of the CPO and SPO samples suggests that a mantle source was enriched due to the interaction of depleted MORB mantle with EMI component and ancient Mariana Trench-like sediment. Utilizing available paleomagnetic data and regional plate reconstruction models, we propose that the CPO represents the Late Eocene back-arc basin fragments formed within the proto-South China Sea. The SPO has a subduction initiation origin and formed in the Sundaland-Eurasian margin in Early Cretaceous. Both ophiolites were emplaced on the Palawan Continental Terrane (PCT) due to the collision of the PCT with Borneo and Cagayan Ridge.